Generation of super-short avalanche electron beams in SF6. (17th April 2014) - Zhang, Cheng; Tarasenko, Victor F.; Shao, Tao; Beloplotov, Dmitry V.; Lomaev, Mikhail I.; Sorokin, Dmitry A.; Yan, Ping
Abstract In this work, the generation of a super-short avalanche electron beam (SAEB) in SF6 in an inhomogeneous electric field is studied on two generators with pulse rise times of 0.5 and 2 ns, respectively. The SAEB parameters in SF6 are compared with those obtained in other gases (air, nitrogen, argon, and krypton). It is shown that the SAEB amplitude in SF6 at pressures ranging from 0.05 to 0.2 MPa is commensurable with that in krypton and is much lower than that in air and nitrogen. It is also found that in SF6, SF6 mixture with 2.5% of nitrogen, and other gases, a diffuse discharge is ignited not only at negative polarity but also at positive polarity of the electrode with small curvature radius. Furthermore, the velocity of the ionization wave front in SF6 in an inhomogeneous electric field is studied. Experimental results show that the velocity of the ionization wave front in SF6 is lower than that in air and nitrogen as well as such velocity decreases when the pressure increases from 0.05 to 0.3 MPa in all gases.